Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/s18124272
|View full text |Cite
|
Sign up to set email alerts
|

An Improved YOLOv2 for Vehicle Detection

Abstract: Vehicle detection is one of the important applications of object detection in intelligent transportation systems. It aims to extract specific vehicle-type information from pictures or videos containing vehicles. To solve the problems of existing vehicle detection, such as the lack of vehicle-type recognition, low detection accuracy, and slow speed, a new vehicle detection model YOLOv2_Vehicle based on YOLOv2 is proposed in this paper. The k-means++ clustering algorithm was used to cluster the vehicle bounding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(84 citation statements)
references
References 27 publications
(28 reference statements)
0
71
0
2
Order By: Relevance
“…The other is a convolutional neural network based on the regression, such as YOLO [24], SSD [25], and YOLOv2 [26], which has continuously improved the calculation speed. Sang et al proposed an improved YOLOv2 to improve detection accuracy and speed [27]. However, there are still tradeoffs between accuracy and speed when using convolutional neural networks for real-time vehicle detection.…”
Section: Introductionmentioning
confidence: 99%
“…The other is a convolutional neural network based on the regression, such as YOLO [24], SSD [25], and YOLOv2 [26], which has continuously improved the calculation speed. Sang et al proposed an improved YOLOv2 to improve detection accuracy and speed [27]. However, there are still tradeoffs between accuracy and speed when using convolutional neural networks for real-time vehicle detection.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this data, Dmitriy Anisimov and Tatiana Khanova [1] have shown that a thoroughly constructed SSD-like detector can run faster than 40 frames per second on the modern CPU while maintaining favourable precision. Another example of good speed-precision trade-off is YOLO v2 architecture [30], which was specialized for vehicle detection via anchors clustering, additional loss normalization, and multi-layer feature fusion strategy.…”
Section: Objects Detectionmentioning
confidence: 99%
“…They generally report higher accuracy in terms of detecting smaller objects in the large image space. Examples include YOLOv2 [41] with improved loss normalization, anchor-box clustering and multi-layer feature fusion [42], YOLOv3 with additional prediction layers [43], Tiny YOLOv3 with repeated up-sampling and additional passthrough layers [44], and focal loss-based RetinaNet [45]. These approaches are performed on relatively low-resolution videos in order to achieve high detection speed and proper accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…These approaches are performed on relatively low-resolution videos in order to achieve high detection speed and proper accuracy. Examples include resolution of 960 × 540 pixels at 34 fps with average precision of 43%-79% [38], resolution of 300 × 300 pixels at 20 fps with mean average precision (mAP) of 77% [39], varying resolutions up to 1920 × 1080 pixels with processing time of 0.09 sec per frame (~11 fps) with F1-score of 39% [40], varying resolutions up to 608 × 608 pixels with processing time of 0.038 sec per frame (~26 fps) with mAP of 68% [42], resolution of 960 × 540 pixels at 9 fps with mAP of 85% [43], resolution of 512 × 512 pixels at 75 fps with mAP of 80%-89% [44], resolution of 960 × 540 pixels at 21 fps with mAP of 74% [45]. A comprehensive report on the performance of single-network detectors against two-stage networks can be found in [46].…”
Section: Related Workmentioning
confidence: 99%